2011
DOI: 10.1371/journal.pone.0026744
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Deficiency Promotes Cardiac Hypertrophy, Dysfunction, and Fibrosis Induced by Pressure Overload

Abstract: Activating transcription factor 3 (ATF3), which is encoded by an adaptive-response gene induced by various stimuli, plays an important role in the cardiovascular system. However, the effect of ATF3 on cardiac hypertrophy induced by a pathological stimulus has not been determined. Here, we investigated the effects of ATF3 deficiency on cardiac hypertrophy using in vitro and in vivo models. Aortic banding (AB) was performed to induce cardiac hypertrophy in mice. Cardiac hypertrophy was estimated by echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 37 publications
8
61
2
Order By: Relevance
“…This basic ZIP family includes the CREB/ATF family of transcription factors, which include CREB, cAMP response (Kehat et al, 2006). Our study and a prior study by Zhou et al (2011) have shown that ATF3 mRNA levels are upregulated 1 day after TAB procedure and that loss of the ATF3 gene can aggravate pressure overload-induced cardiomyopathy in mice. In addition, we observed that although the nuclear translocation of ATF3 occurred for only a short duration (1 day after TAB procedure), ATF3 protein remained which were transiently cotransfected with indicated plasmids.…”
Section: Discussionsupporting
confidence: 63%
“…This basic ZIP family includes the CREB/ATF family of transcription factors, which include CREB, cAMP response (Kehat et al, 2006). Our study and a prior study by Zhou et al (2011) have shown that ATF3 mRNA levels are upregulated 1 day after TAB procedure and that loss of the ATF3 gene can aggravate pressure overload-induced cardiomyopathy in mice. In addition, we observed that although the nuclear translocation of ATF3 occurred for only a short duration (1 day after TAB procedure), ATF3 protein remained which were transiently cotransfected with indicated plasmids.…”
Section: Discussionsupporting
confidence: 63%
“…15,16 Cardiac function was determined by transthoracic echocardiography and hemodynamic analysis. 17 Excised hearts were arrested in diastole with 10% KCl, weighed, fixed by perfusion with 10% formalin, and embedded in paraffin for histological studies or were frozen for RNA and protein extraction. Sca-1 expression was determined using Western blotting, immunohistochemistry, and immunofluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…AB was performed as described previously [12][13][14] ; all of the mice used in our studies were 8-10-week-old males with a body weight of 23.5-27.5 g. Eight weeks following AB, the body weight, heart weight, lung weight and tibial length (TL) of the mice were measured to compare the heart weight/body weight (HW/BW, mg/g), lung weight/body weight (LW/BW, mg/g), and heart weight/TL (HW/TL, mg/mm) ratios.…”
Section: Animals and Animal Modelsmentioning
confidence: 99%